COVID-19-Associated Neurological Complications in Children: COVID-19 associated neurological complications - Shenoy, Sangeetha; Nagabushana, Divya; Kumar BM, Sunil; AR, SOMASHEKAR; Rao, Chandrika (Iranian Journal of Child Neurology, 2024)
Objective Neurological manifestations of Severe Acute Respiratory Syndrome coronavirus-2 have been well documented in adults during and after infection with the virus as well as after vaccination. The incidence of severe neurological symptoms among children is very low. This study aimed to analyze the varied neurological manifestations after COVID-19 infection among children and give a report on a single center experience with these severe neurological symptoms Materials & Methods Case records of patients less than 18 years admitted between July 2021 to December 2022 with neurological manifestations and COVID-19 infection or with elevated COVID-19 antibodies after exclusion of other etiological diagnosis were analyzed. Results There were 10 cases in the age range of 1-15 years. All the cases had elevated COVID-19 antibodies with history of contact 2-3 weeks prior except one who was positive for COVID-19 infection. Two cases presented with acute ascending paralysis suggestive of Guillain-Barre syndrome. Four cases presented with features of encephalopathy with clinical presentation fulfilling the criteria of Multisystem inflammatory syndrome in children. One case presented with fever and focal seizures with MRI showing sagittal sinus thrombosis, and one presented with fever and altered sensorium with MRI showing leukoencephalopathy. One child had cerebral mucormycosis without any evidence of immunosuppression. There was one child with features of encephalopathy with active COVID-19 infection. Conclusion The varied presentation highlights the central and peripheral nervous system involvement by the virus in the pediatric population. It also emphasizes the need to investigate for COVID-19 in children presenting with these complaints during the pandemic.